Railway transportation systems design, construction and operation - Pyrgidis, Christos N. (CRC Press, Taylor & Francis Group, 2022)
"This comprehensive overview covers the entire range of railway passenger systems, from conventional and high-speed intercity systems to suburban, regional, operating on steep gradients, and urban ones. New material provides innovations in rail freight transportation, case studies, and an update of cutting-edge technologies"--